Pengetahuan dan Sikap terhadap Situasi Bencana dan Kegawatdaruratan: Sebuah Studi Multisenter - Vito Filbert Jayalie; Beryliana Maya Anisa; Rania Zahra; Luther Holan Parasian; Caren Andika Surbakti; Nela Lutfiana; Adrian Reynaldo Sudirman; Lintang Sekar Sari; Indah Nur Rachmah; Hasna Ibadurrahmi; M. Sopiyudin Dahlan; Riyadh Firdaus; Indonesia Emergency Knowledge; Attitude Evaluator Team (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction: Being in the ring of fire have caused Indonesia prone to emergency and disasters. This condition should make a positive correlation to level of citizen’s knowledge and attitude towards emergency and disaster situation. However, there is no study to assess this condition. This study aims to assess the knowledge and attitude of Indonesian in emergency and disaster using a cross-sectional study collected from questionnaire interviewed by trained medical students in four centers (Jakarta, Depok, Padang, and Makassar).Method: Samples were collected using random cluster sampling. Out of 570 samples participated, most of the respondents had a poor knowledge (56.1%) and attitude (60.7%). Result: There is a significant relationship between knowledge and attitude (p less than 0.001). Age, education, and training on disaster can affect both knowledge and attitude towards emergency and disaster situation (p less than 0.05). However, disaster experience only had a significant contribution towards knowledge (p less than 0.05) but not the attitude (p = 0.856). Conclusion: Most of the population in this study had poor knowledge and attitude in emergencies. These presented data also indicate that training on disaster is urgently needed to give impact on citizen’s awareness. Moreover, further research is needed.